Seasonality and Capacity An Application to Italy - Mini, Federico (International Monetary Fund, 2000)
Information on seasonal frequencies can provide valuable insights for understanding economic fluctuations. This is particularly true for Italy, where the variability of production in manufacturing is extremely high and almost entirely due to seasonal factors. This paper discusses the option of exogenous seasonality resulting from changes in underlying technology and preferences, versus the possibility of endogenous seasonality arising because of synergies across agents. It then highlights the size of the seasonally-driven capacity slack and discusses its relevance from a welfare standpoint